Teacher Strategies for Increasing Student Creativity Through the Project for Strengthening Pancasila Student Profiles - Salsabila, Belinda; Sukartono, Sukartono (International Conference on Education for All, 2024)
There are still many students who lack imagination when creating work. This is a problem that indicates that childrens creativity is still low. A project to improve the profile of Pancasila students (P5) is one strategy that teachers can use. This research aims to describe teachers strategies for increasing creativity in grade 5 through a project to strengthen the profile of Pancasila students at State Elementary School 3 Sawahan and to describe the supporting factors and obstacles as well as solutions implemented by teachers in implementing the project to strengthen the profile of Pancasila students. This type of research uses descriptive qualitative research with a phenomenological model. Class 5 teachers and students are the subjects of this research. The data collection techniques used were observation, interview sheets, and documentation. The validity of the data was tested using triangulation of sources and techniques. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. The findings of this study demonstrate that project-based learning and differentiation learning are two strategies that teachers can use to foster student creativity. Adequate school media facilities and school environmental issues are the driving factors behind the implementation of the project to strengthen the profile of Pancasila students. Meanwhile, the obstacles experienced by teachers lie in the scheduling of implementation not being as specified. For this reason, a solution is needed to overcome these obstacles by changing the schedule of the project to strengthen the profile of Pancasila students.